PEMBAGIAN HAK WARIS BAGI AHLI WARIS NON MUSLIM DARI PERKAWINAN BEDA AGAMA ATAS PEWARIS MUSLIM DITINJAU BERDASARKAN HUKUM ISLAM - Emmanuella R.R Sinaga (2022)
The study aims to analyze arrangements regarding the inheritance rights of religious marriages in view of Islamic law and settlement efforts regarding the division of inheritance rights that provide justice for non-Muslim heirs of Muslim heirs. The issue of inheriting different religions today is a contemporary problem, because both in the Qur'an and hadith there is no explanation of the property part for heirs of different religions. The method of approach in this study uses normative juridical. The results showed that arrangements regarding the inheritance rights of children of different religions according to Islamic law are regulated in hadith and KHI where non-Muslim children are not entitled to inheritance. But in practice, in the court's decision the judge still gives a share of inheritance to children of different religions based on compulsory wills. This is contrary to the terms of Islam and KHI. However, the decision to grant the inheritance is to realize justice, benefit and legal certainty in family life. Settlement efforts regarding the division of inheritance rights from different religions according to Islamic law are by means of grants and wills. This is in accordance with the provisions of the Qur'an, hadith and KHI which in terms of grants are allowed to both Muslims and non-Muslims. While the will is used by the judge in court rulings related to the division of inheritance.